2011
DOI: 10.1002/jts.20698
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the trauma experience of women immigrants from Central America, South America, and Mexico

Abstract: Trauma has been understudied among Latina immigrants from Central and South America. This study examined the types and context of trauma exposure experienced by immigrant women from Central America, South America, and Mexico living in the United States. Twenty-eight women seeking care in primary care or social service settings completed life history interviews. The majority of the women reported some type of trauma exposure in their countries of origin, during immigration, and/or in the United States. In the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 14 publications
0
58
3
Order By: Relevance
“…The intervention was designed to be simultaneously responsive to patients’ preferences for individual psychotherapy, to the need of primary care clinics that serve the uninsured for cost- and time-efficient services, and to address the social isolation that is so common to the Latina immigrant experience. Developed based on findings from the research team’s formative research (Kaltman et al, 2011; 2014; Hurtado de Mendoza et al, 2014), the resulting intervention, Latinas Saludables, incorporated both individual and group sessions. The goals of the individual sessions were to reduce symptoms and to address group readiness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention was designed to be simultaneously responsive to patients’ preferences for individual psychotherapy, to the need of primary care clinics that serve the uninsured for cost- and time-efficient services, and to address the social isolation that is so common to the Latina immigrant experience. Developed based on findings from the research team’s formative research (Kaltman et al, 2011; 2014; Hurtado de Mendoza et al, 2014), the resulting intervention, Latinas Saludables, incorporated both individual and group sessions. The goals of the individual sessions were to reduce symptoms and to address group readiness.…”
Section: Discussionmentioning
confidence: 99%
“…First, to understand and contextualize Latinas’ traumatic experiences and their help seeking behaviors, Latina immigrants (primarily from Central and South America) who were seeking care in the primary care clinics were interviewed in-depth. In addition to being exposed to a myriad of traumatic experiences (Kaltman et al, 2011), women reported feeling lonely and isolated and lacking a strong social network they could rely on, as they encountered several barriers to developing and maintaining social relationships in the US (Hurtado de Mendoza et al, 2014). …”
Section: Description Of the Latinas Saludables Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like in this, few women have reported sexual violence in intimate relationships. Women's stories suggest that sexual violence, in the context of intimate relationships, is not often discussed, especially in specific research surveys on the subject [29]. Emotional abuse and psychological violence were the main types revealed by the women interviewed.…”
Section: Discussionmentioning
confidence: 98%
“…Questions were modified from a trauma exposure measure used in the collaborative care clinic at intake (Kaltman et al, 2011). …”
Section: Methodsmentioning
confidence: 99%